Determining the effect of cognitive-behavioral therapy, desensitization with eye movements and reprocessing and biofeedback on migraine attacks (frequency, duration and intensity), anxiety sensitivity, sleep quality and quality of life of women with Migra - Mehrmanesh, Elahe; Hejazi, Fariba; Ehteshamzadeh, Parvin; Bakhtiarpour, Saeed (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study is to determine the effect of cognitive-behavioral therapy, desensitization with eye movements and reprocessing and biofeedback on migraine attacks (frequency, duration and intensity), anxiety sensitivity, sleep quality and quality of life of women with migraine. Method: The research was semi-experimental and was conducted using a pre-post test and follow-up design with a control group. The statistical population included all women who referred to Tehran's Vision of the Future Clinic in 2019 due to headache. Among the people who were diagnosed with migraine, 60 people were selected and randomly divided into 3 experimental groups and one control group. Then the people of the cognitive-behavioral group underwent group therapy for 11 sessions of 90 minutes each week, and the people of the desensitization group with rapid eye movements and reprocessing individually in 3 sessions of 90 minutes and once a week, and the people of the biological feedback treatment group were treated for 15 sessions in 3 weeks of 45 minutes. The data was analyzed by SPSS-25 software and by multiple variance analysis. Results: Based on the results of this research, it can be stated that cognitive-behavioral therapy, desensitization with eye movements and reprocessing and biofeedback are effective on attacks (frequency, duration and intensity), anxiety sensitivity, sleep quality and quality of life of women